Survey on Testing of BPEL Processes (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Software testing is very important phase in any development Life Cycle. The test Case generation is critical task in any type of testing. The automation of test case generation is necessary to reduce cost and effort incurred in the testing of large software. Testing of the BPEL processes is new area of research and the automation of the test cases is necessary in order to find bugs in the processes and reduce the cost of theÂ  testing businessÂ  processes .This paper focuses on the survey of the testing techniques used to test the BPEL processes.